Circadian influence on change in body fluid during exercise - Wang, R.; Zhao, R.; Shi, X.; Shi, X. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose is to investigate the circadian influence on the changes in body fluid during exercise. Result: The effect of the circadian rhythm on body fluid response to exercise was significant. Greater dehydration occurred during exercise in the morning, despite significantly less UV or Na+ excretion.